Degradation Products of Bran Phytate Formed during Digestion in the Human Small Intestine: Effect of Extrusion Cooking on Digestibility - Sandberg, Ann-Sofie; Andersson, Henrik; Carlsson, Nils-Gunnar; Sandström, Brittmarie (The Journal of nutrition, 1987)
To investigate the digestion of phytate in the stomach and small intestine in humans, studies were performed in subjects with established ileostomy. A recently developed high performance liquid chromatography method made it possible to analyze phytate and its degradation products in food and digesta. The digestibility of phytate in raw bran and extruded bran was investigated in seven ileostomy patients. Each subject was studied for two 4-d periods while consuming a constant low fiber diet with the addition of either 54 g/d of a bran-gluten-starch mixture or the corresponding extruded product. During passage through the subject’s stomach and small intestine 58%, on average, of the phytate in unprocessed bran was hydrolyzed to inositol penta-, tetra- and triphosphates. When bran was subjected to extrusion cooking, 25% of the inositol hexaphosphate was hydrolyzed to penta- and tetra-phosphate and the phytase activity ceased. Essentially no phytate digestion occurred when the ileostomy subjects consumed the extruded product. The reduced digestibility might be due to the lost phytase activity or to formation of indigestible phytate complexes during extrusion cooking.